2018
DOI: 10.3389/fneur.2018.00975
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mild Cognitive Impairment From Speech in Swedish Using Deep Sequential Neural Networks

Abstract: While people with mild cognitive impairment (MCI) portray noticeably incipient memory difficulty in remembering events and situations along with problems in decision making, planning, and finding their way in familiar environments, detailed neuropsychological assessments also indicate deficits in language performance. To this day, there is no cure for dementia but early-stage treatment can delay the progression of MCI; thus, the development of valid tools for identifying early cognitive changes is of great imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…In recent years, machine learning approaches with datadriven algorithms have been used to combine and classify brain features. Some classifiers such as support vector machines (SVMs) (Prasad et al, 2015;Khazaee et al, 2016), Naïve Bayes (Zhuo et al, 2018) and deep neural networks (Themistocleous et al, 2018) are applied to discriminate normal controls from subjects with MCI. However, most of these methods focus on a single modality of imaging, the functional connectome, or graph theory attributes separately, resulting in relatively poor classification performance (Suk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, machine learning approaches with datadriven algorithms have been used to combine and classify brain features. Some classifiers such as support vector machines (SVMs) (Prasad et al, 2015;Khazaee et al, 2016), Naïve Bayes (Zhuo et al, 2018) and deep neural networks (Themistocleous et al, 2018) are applied to discriminate normal controls from subjects with MCI. However, most of these methods focus on a single modality of imaging, the functional connectome, or graph theory attributes separately, resulting in relatively poor classification performance (Suk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The collaboration with Dr. Dimitrios Kokkinakis and colleagues within the project 'Linguistic and extra-linguistic parameters for early detection of cognitive impairment' (Kokkinakis et al, 2016) is an important next step to further refine the study of cognitive functioning in relation to dementia progression, using novel technical and analytical tools other than traditional neuropsychological testing; see for instance Fraser et al (2017); Themistocleous et al (2018) and Linz et al, (2019).…”
Section: Current σAtus and The φTure Of The Gothenburg MCImentioning
confidence: 99%
“…In recent years, deep neural network (DNN) has garnered clinical interests in cognitive diagnostic applications due to its advantages in efficient classification. Moreover, many existing methods have been proposed, where some of them [4]- [7] combine DNN with neuroimaging markers, while other methods [8]- [10] combine DNN with neuropsychological assessments. Jain et al [5] proposed a transfer learning approach for accurately classifying brain sMRI slices amongst 3 different classes: Alzheimer's disease (AD), cognitively normal(CN) and mild cognitive impairment (MCI).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the model could accurately predict MCI and AD type dementia on a very sparse clinical language dataset. Themistocleous et al [10] provided an automated deep learning method using DNN architectures that identified individuals with MCI from healthy controls. However, there are still limitations in the current studies.…”
Section: Introductionmentioning
confidence: 99%